EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI), GROUP INVESTIGATION (GI), DAN PEMBELAJARAN LANGSUNG PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS VIII SMP NEGERI SE-KOTA SURAKARTA - Meilasari, Venty; Budiyono, Budiyono; Slamet, Isnandar (Journal of Mathematics and Mathematics Education, 2016)
Abstract: This research aimed to find out: (1) which one providing better mathematics learning achievement, TAI model, GI model or direct instruction model, (2) which one providing better mathematics learning achievement, the high, medium or low independence of learning students, (3) in each learning models, which one providing better mathematics learning achievement, the high, medium, or low independence of learning students, (4) in each categories of independence of learning, which one providing better mathematics learning achievement, TAI model, GI model or direct instruction learning model. This research used the quasi-experimental research method. The research design was a 3×3 factorial design. The population were all students of the eight class of junior high school in Surakarta on academic year 2015/2016. The sample was taken using stratified cluster random sampling and consisted of 281 students. The instruments used were independence of learning questionnaire and mathematics achievement test. The proposed hypothesis of the research were analyzed by using two-way analysis of variance with unbalanced cells. The conclusions of this research were as follow. (1) TAI model provided the mathematics achievement as good as GI model, TAI model and GI model provided better mathematics achievement than direct instruction model. (2) The high independence of learning student had better mathematics achievement than medium and low independence of learning students, and the medium had better than low independence of learning students. (3) In TAI model and direct instruction model, the high, medium, and low independence of learning had the same mathematics achievement, in GI learning model, the high independence of learning students had mathematics achievement as good as the medium independence of learning students, the high independence of learning had better than the low independence of learning, and the medium independence of learning students had the same as the low independence of learning students. (4) In high and low independence of learning, TAI model, GI model, and direct instruction model provided the same achievement, in medium independence of learning, TAI model and GI model provided the same achievement, TAI model provided better achievement than direct instruction model, GI model was the same as direct instruction model.Keyword: TAI, GI, Direct Instruction, Independence of Learning, and Mathematics Achievement